Homophobic violence: systematic literature review (Research, Society and Development, 2020)
Homophobia is the hate against homosexual, and the actions of intolerance that results in violent processes. The objective of this study is to carry out a systematic review of the literature, with the selection of the main articles found in the databases of the CAPES Portal, that show a quantitative study on homophobic violence. The search was done in the last five years, from January 1, 2015 to December 31, 2019. The descriptors used were "homosexuals", "LGBT", "gays", "violence", "murders", "deaths", “homicides” combined. Inclusion criteria were publications in article format, free, without language specification, with search for descriptors contained in subject, title and author [any]. Exclusion criteria were publications that did not fit into the article modality, those that were published outside the defined time frame, and those that did not present quantitative research. Six articles were found, one of them in Spanish, which showed a certain similarity in the pattern of the identified violence, highlighting psychological aggressions. It is concluded that the amount of research found is still inexpressive, especially when considering the lack of official data on the subject.